Influence of plasma impurities on the fuel retention in tungsten. (28th June 2019) - Kreter, A.; Nishijima, D.; Doerner, R.P.; Freisinger, M.; Linsmeier, Ch.; Martynova, Y.; Möller, S.; Rasinski, M.; Reinhart, M.; Terra, A.; Torikai, Y.; Unterberg, B.
Abstract: The retention of radioactive tritium in the reactor wall is a safety issue and should be kept to a minimum. We investigated the influence of helium, argon, neon and nitrogen as plasma impurities on the deuterium retention in tungsten in the linear plasma devices PSI-2 and PISCES-A. Following mixed plasmas were produced: pure D, D  +  He, D  +  Ar, D  +  Ne, D  +  N and D  +  He  +  Ar, with impurity fractions between 3% and 10%. Experiments were performed at tungsten sample temperatures of 500 and 770 K. The incident ion energy was 70 eV, above the tungsten sputtering threshold for argon and nitrogen, but below it for deuterium and helium. For neon, in addition, it was varied between 20 and 70 eV, below and above the tungsten sputtering threshold, respectively. The admixture of helium reduced the deuterium retention by a factor of 3–100, with a stronger reduction at a higher sample temperature. In the D  +  He  +  Ar case the retention was similar as for pure D. Argon sputtered the near-surface helium nanobubble layer and thus overrode the effect of helium. The effect of neon is sensitive to the incident ion energy. Addition of nitrogen increased the deuterium retention by a factor of ~10 and ~100 for 500 and 770 K, respectively. In general, the effect of impurities on the deuterium retention appears to be sensitive to the properties of the affected near-surface layer of tungsten. Admixed species, i.e. helium, can form a layer with open porosity, which serves as an additional release channel for deuterium thus decreasing the retention. However, if the process is dominated by sputtering, as for argon, such a layer cannot be formed. The nitrogen enriched layer, in contrast, serves as a desorption barrier for deuterium increasing the retention.